2012
DOI: 10.1590/s0100-06832012000400005
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal inoculation increases biomass of Euterpe edulis and Archontophoenix alexandrae after two years under field conditions

Abstract: SUMMARYInoculation with arbuscular mycorrhizal fungi (AMF) of tree seedlings in the nursery is a biotechnological strategy to improve growth, survival after transplanting, biomass production and to reduce the use of fertilizers. Archontophoenix alexandrae and Euterpe edulis are palm species used in southern Brazil to produce the palm heart, the latter being included in the list of threatened species due to the overexploitation of its native population. The purpose of this paper was to evaluate the effect of my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
(33 reference statements)
1
5
0
Order By: Relevance
“…When exposed to salt stress, plants inoculated with AM had higher biomass than non-mycorrhizal cuttings, which agreed with the previous studies (Ramos-Zapata et al 2009;Sgrott et al 2012). The positive effects of AMF on males and females biomass were magnified by salt stress, which was consistent with Sheng et al (2009).…”
Section: Discussionsupporting
confidence: 91%
“…When exposed to salt stress, plants inoculated with AM had higher biomass than non-mycorrhizal cuttings, which agreed with the previous studies (Ramos-Zapata et al 2009;Sgrott et al 2012). The positive effects of AMF on males and females biomass were magnified by salt stress, which was consistent with Sheng et al (2009).…”
Section: Discussionsupporting
confidence: 91%
“…These results are consistent with those of Morte and Honrubia (2002) who found that the height and dry weight of Phoenix canariens inoculated with Glomus deserticola and G. intraradices were not different from those of uninoculated control. Sgrott et al (2012) also found in their study that AMF had no significant effect on plant height but increased total biomass. In addition, inoculation with Ga decreased nodulation parameters and root dry weight of peanut in comparison to control plants.…”
Section: Plant Response To Mycorrhizal Inoculationmentioning
confidence: 82%
“…When subjected to salt stress, maize plants showed obvious decrease in both leaf area and biomass, such reduction was possibly related to appearance of osmotic stress and increase on the efficiency for ion transfer (Farooq et al, 2009). Meanwhile, both higher leaf area and biomass were detected in AM plants (Ramos-Zapata et al, 2009;Sgrott et al, 2012), it can be explained that AMF might change biomass allocated to aboveground and belowground (Zhang et al, 2011). And the positive influence may also be a result of the enhancement of ability of nutritive equilibrium, absorbance, metabolism and utilization caused by mycorrhiza (Zandavalli et al, 2004).…”
Section: Discussionmentioning
confidence: 98%